2013
DOI: 10.1002/mds.25389
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hallucinations in Parkinson's disease: Results from a large prospective cohort study

Abstract: The aim of this study was to identify risk factors for the development of hallucinations in patients with Parkinson's disease (PD). A broad range of motor and nonmotor features was assessed at baseline and during the following 5 years in 386 PD patients. Cross-sectional analyses of baseline data and longitudinal analyses of follow-up data were performed to identify risk factors for hallucinations in PD. Twenty-one percent of the patients had hallucinations at baseline, whereas 46% of the patients without hallu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 44 publications
5
48
1
1
Order By: Relevance
“…Secondly, high intravenous doses of levodopa did not provoke hallucinations (but induced peak-dose dyskinesia) in advanced patients with PD with daily hallucinations (18). Finally, studies investigating risk factors for hallucinations in PD have reported that daily levodopa dose or levodopa equivalent doses are not independent risk factors for hallucinations in multivariate analyses (19,20). However, it is known that hallucinations can be triggered in some patients with PD by dopaminergic medications including adding entacapone to the existing levodopa therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Secondly, high intravenous doses of levodopa did not provoke hallucinations (but induced peak-dose dyskinesia) in advanced patients with PD with daily hallucinations (18). Finally, studies investigating risk factors for hallucinations in PD have reported that daily levodopa dose or levodopa equivalent doses are not independent risk factors for hallucinations in multivariate analyses (19,20). However, it is known that hallucinations can be triggered in some patients with PD by dopaminergic medications including adding entacapone to the existing levodopa therapy.…”
Section: Discussionmentioning
confidence: 97%
“…These clinical signs and symptoms are present in AD as well as in dementia with Lewy bodies (DLB) [6] and in Parkinson's disease (PD) [7], with these three entities also sharing neuropathological features. The brains of patients clinically diagnosed with AD often have Lewy bodies in addition to amyloid plaques and neurofibrillary tangles.…”
Section: Introductionmentioning
confidence: 99%
“…Hallucinations are the most common psychotic symptom in PD patients [29][30][31]. They occur in about 20-30% of drugtreated patients [30,32]. The hallucinations are typically visual, but auditory occur about half as commonly.…”
Section: Psychosismentioning
confidence: 99%